Assessment of S.A.R. warehousing activities: a proposal for improvements - Medeiros, Alexandra de Melo (2018)
The logistics market has been evolving over the years as well as its importance and the role it has been performing in every human and organization’s life. This master thesis is a project developed about Sociedade Açoreana de Representações, Ltda. (S.A.R.), that is one of the 1.162.069 Portuguese SME (Small and Medium Enterprises) representing 99,9% of the Portuguese business market. S.A.R. operates in the non-specialized wholesale trade industry and it is responsible for product’s distribution of exclusive and own brands in Azores. This project is under the logistics study and, through the analysis of its warehousing activities, mainly the storing and picking activity, aims to propose improvement solutions. In order to deliver value-added suggestions, information about the described activities and warehouse layout were collected with the goal of forecasting orders through different techniques. Afterwards, the analyzed families were allocated in the storing area through two different criteria, the ABC turnover rate of the forecasted orders as well as the COI criteria, according to the dedicated and class-based storage methods. The final step of this project was to assess the performance of each storage model and compare it with S.A.R.’s current allocation of products, through the distance travelled by pickers. Results demonstrated that it is possible to improve S.A.R.'s current performance, between 47% and 66%, depending on the criteria and methods applied. These results represent an improvement between 2.298.720 and 3.192.144 travelled meters, considering the forecasted orders between July 2017 and June 2018